Analysis of multi-field coupling behaviors of sandwich piezoelectric semiconductor beams under thermal loadings - Kong, Dejuan; He, Zhuangzhuang; Liu, Chengbin; Zhang, Chunli (Applied mathematics and mechanics, 2025)
Sandwich piezoelectric semiconductor (PS) structures have significant applications in multi-functional semiconductor devices. The analysis of multi-field coupling behaviors of PS structures is of fundamental importance in developing novel PS devices. In this paper, we develop a general temperature-deformation-polarization-carrier (TDPC) coupling model for sandwich-type PS beams involving pyroelectricity under thermal loadings, based on three-dimensional (3D) basic equations of the thermo-piezoelectric semiconductor (TPS). We derive analytical solutions for extensional, bending, and buckling deformations of simply-supported sandwich n-type PS beams subjected to open-circuit and electrically isolated boundary conditions. The accuracy of the proposed model in this paper is verified through finite element simulations implemented in the COMSOL software. Numerical results show that the initial electron concentration and the thickness ratio of the PS layer to the beam’s total thickness have a significant effect on thermally induced extensional and bending responses, as well as critical buckling mechanical and thermal loadings. This study provides a theoretical framework and guidance for designing semiconductor devices based on sandwich PS beam structures.